Efektivitas Model Pembelajaran Kooperatif Tipe Numbered Head Together Terhadap Hasil Belajar Siswa pada Materi Sistem Ekskresi Manusia di Kelas XI IPA SMA Negeri 1 Air Joman T.P. 2016/2017 - Lestari, Eka; Hasanah, Uswatun; Siregar, Dahliana (Universitas Negeri Medan, 2017)
The aim of research is to know the effectiveness implementation of cooperative learning model type Numbered Head Together (NHT) to student learning outocomes in learning human excretion system in class XI IPA SMA Negeri 1 Air Joman Academic Year 2016/2017. This type of research is a pre experimental. The research was conducted from April to Juni 2017. The samples included 33 people. The instrument used to collect data is multiple choice objective test consisting of 35 question. The results showed that the application of cooperative learning model type Numbered Head Together (NHT) on subject matter of human excretion system can improve students mastery of subject matter that is â¥75%, the level of classical learning completeness 0f 94%, and the achievement of all indicators has ben fulfilled, namely 100%. Thus the implementation of cooperative learning model type Numbered Head Together (NHT) categorized effective in learning human excretion system in CLASS XI IPA SMA Negeri 1 Air Joman Academic Year 2016/2017.